GRADING FIGURE BETWEEN OLD AND NEW INDONESIAN DANGDUT SONGS IN APPRAISAL THEORY - Chalimah Chalimah (Universitas Sebelas Maret, 2023)
The study is conducted to investigate the grading figure between old and new Indonesian Dangdut Songs. The data are grouped in high, median, and low grading to see the linguistic features used in the songs to find the attractive model used to get the listeners’ interest by using appraisal theory. The data are chosen in purposive sampling that meets the objective to choose songs that are well known in Indonesian people. The result shows that the old Indonesian Dangdut songs tend to use high grading to attract the listeners’ emotional feeling as much as 77% and the rest uses median grading, and very minor in using low grading. The high grading in old songs is dominant to use high grading in manner degree in metaphor while the rest uses high grading in frequency, in manner degree and in intensifier. The new Indonesian Dangdut songs tend to be more various in using grading figure and are dominant both in using median grading in the form of attitudinal lexis and high grading in metaphor as much as 71% and the rest uses other grading figures. It recommends for further study to see from different point of view in pragmatics field since this study sees in systemic functional linguistics field.